Seismic Monitoring of a Subarctic River: Seasonal Variations in Hydraulics, Sediment Transport, and Ice Dynamics - Polvi LE; Dietze M; Lotsari E; Turowski JM; Lind L (American Geophysical Union, 2022)
High-latitude rivers are commonly covered by ice for up to one third of the year. Our understanding of the effects of ice on channel morphodynamics and bedload transport is hindered by the difficulties of sensing through the ice and dangers of field work on thin ice or during ice break-up. To avoid this drawback, we used seismic signals to interpret processes and quantify water and sediment fluxes. Our objective was to determine seasonal differences in hydraulics and bedload sediment transport under ice-covered versus open-channel flow conditions using a small seismic network and to provide a first-order estimation of sediment flux in a Fennoscandian river. Our study reach was on a straight, low-gradient section of the Savar River in northern Sweden. Interpretations of seismic signals, from a station 40 m away from the river, and inverted physical models of river stage and bedload flux indicate clear seasonal differences between ice-covered and open-channel flow conditions. Diurnal cycles in seismic signals reflecting turbulence and sediment transport are evident directly after ice break-up. Analysis of seismic signals of ice-cracking support our visual interpretation of ice break-up timing and the main ice break-up mechanism as thermal rather than mechanical. Assuming the bulk of sediment moves during ice break-up and the snowmelt flood, we calculate a minimum annual sediment flux of 56.2 +/- 0.7 t/km(2), which drastically reduces the uncertainty from previous estimates (0-50 t/km(2)) that exclude ice-covered or ice break-up periods.